Analysis of lectin-bound glycoproteins in snake venom from the Elapidae and Viperidae families - Nawarak J. (2014)
This paper describes an efficient method of studying the glycoproteins found in snake venom. The glycosylation profiles of the Elapidae and Viperidae snake families were analyzed using FITC-labeled lectin glycoconjugates. The Con A-agarose affinity enrichment technique was used to fractionate glycoproteins from the N. naja kaouthia venom. The results revealed a large number of Con A binding glycoproteins, most of which have moderate to high molecular weights. To identify the proteins, the isolated glycoprotein fractions were subjected to two-dimensional electrophoresis and MALDI-TOF MS. Protein sequences were compared with published protein databases to determine for their biological functions.